“Because they have technology”: A comparative study of sustainable development discourses among secondary school teachers in Tanzania and Norway - Mellingen, Øyvind K. (Nordic Journal of Comparative and International Education (NJCIE), 2024)
Over the last forty years, the concept of sustainable development has gained attention in large parts of the world. With it comes the need for comparative research on how the concept is understood in different contexts. This article is a comparative discourse analysis of how Tanzanian and Norwegian secondary school teachers conceptualize sustainable development. By applying Laclau and Mouffe’s (2014) discourse apparatus, I trace articulations of sustainable development across Tanzanian and Norwegian discourses. The findings indicate that the Tanzanian teachers in the study primarily conceptualize sustainable development within a socioeconomic discourse, while the Norwegian teachers are rooted in an environmental discourse. The teachers are also embedded in a Western exceptionalism discourse constructed around the myth of “the West” as sustainable, and favour solutions emerging from Western technology and innovation. However, the study also finds that there is a critical discourse opposing this articulation of “the West”.